2002
DOI: 10.1080/00039890209601411
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health Effects in New York City Firefighters after Exposure to Polychlorinated Biphenyls (PCBs) and Polychlorinated Dibenzofurans (PCDFs): The Staten Island Transformer Fire Health Surveillance Project

Abstract: Following an electrical transformer fire in Staten Island, New York, a health surveillance program was established for 60 New York City firefighters and emergency medical technicians exposed to polychlorinated biphenyls (PCBs) and polychlorinated dibenzofurans (PCDFs). Exposure potential was documented after high levels of PCBs and PCDFs were found on transformer and firefighters' uniforms. Personnel received comprehensive medical examinations, and the results were compared with preexposure values. Serum was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Further kinetic data are needed to understand the relationship of exposure to burning plastics under various exposure conditions with internal dose levels. One report of firefighters after exposures to a transformer fire found 1,2,3,4,6,7,8-heptachlorodibenzofuran and 1,2,3,4,6,7,8-heptachlorodibenzodioxin to have the highest average blood levels, with the exception of the fully chlorinated octa class compounds (Kelly et al 2002). These findings are also consistent with the general U.S. population data showing the octa and hepta congeners to be among the most detectable (CDC 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Further kinetic data are needed to understand the relationship of exposure to burning plastics under various exposure conditions with internal dose levels. One report of firefighters after exposures to a transformer fire found 1,2,3,4,6,7,8-heptachlorodibenzofuran and 1,2,3,4,6,7,8-heptachlorodibenzodioxin to have the highest average blood levels, with the exception of the fully chlorinated octa class compounds (Kelly et al 2002). These findings are also consistent with the general U.S. population data showing the octa and hepta congeners to be among the most detectable (CDC 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that average daily intake of PCBs by human beings via ambient air is about 100 ng, and average daily intake via drinking water is Ͻ200 ng (7). The average serum PCB levels for general population is about 1 to 2 parts/billion (ppb) (30,33), whereas in occupationally exposed populations the PCB levels are more than 4 ppb (30, 33). Roya et al (52) detected blood PCB concentration in women with endometriosis and found that women with stage IV endometriosis had a blood PCB29 concentration of 0.99 Ϯ 0.54 ppb.…”
Section: Discussionmentioning
confidence: 99%
“…Job-specific means that the measured aspect is a risk for the health or safety of the employee or the public, due to the tasks in the job. Some of the different aspects covered in this study were the traditional WHS, as measuring late responses to exposure in real work (Winwood et al 2009;Levin et al 2004;Wright et al 2002;Greven et al 2009;McDiarmid et al 2007;Vimercati et al 2006;Kelly et al 2002). However, some less traditional aspects of WHS were covered also and the job specificity of some of these studies might need some explanation.…”
Section: Discussionmentioning
confidence: 89%
“…For the environmental exposure studies, the reasons for starting a WHS activity were job-specific; however, in some of those studies, not always a clear description was made by the authors of the relation between the job requirements and the measurement (i.e. in Levin et al 2004;Kelly et al 2002). In the intervention studies, it was clear how the interventions related to the job.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation